Analysis of the Validity of PBL-Based Interactive Teaching Materials on Materials Respecting Diversity in Grade IV Elementary School - Azzahra, Atthahirah; Reinita , Reinita (Journal of Educational Sciences, 2025)
Education aims to develop the potential of students as a whole, covering the cognitive, psychomotor, and affective realms, one of which is realized through learning Pancasila Education. As an important subject at every level, Pancasila Education is expected to encourage active learning. However, the implementation is often monotonous with the dominance of printed books, so students are less encouraged to delve into the material and depend on teachers. This research aims to develop interactive teaching materials for Respecting Diversity material that are feasible for use in Grade IV of elementary school to increase activeness while accommodating students' learning needs. The method applied is in the form of research and development with the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. Validation was conducted by three experts: material, media, and language. Results indicated scores of 86% from material experts, 86.7% from media experts, and 92% from linguists, with an overall average of 88.23%, categorized as highly valid. These findings show that the PBL-based interactive teaching materials developed are feasible for use in learning, are able to relate the material to the context of real problems, and have the potential to increase students' engagement and critical thinking skills.